Advances in drug treatments for mesothelioma. (24th May 2022) - Zucali, Paolo Andrea; De Vincenzo, Fabio; Perrino, Matteo; Digiacomo, Nunzio; Cordua, Nadia; D'Antonio, Federica; Borea, Federica; Fazio, Roberta; Pirozzi, Angelo; Santoro, Armando
ABSTRACT: Introduction: The paucity of the therapeutic armamentarium currently available for patients with malignant mesothelioma clearly represents a huge unmet need. Over the last years, based on new advances in understanding the biology of mesothelioma, new therapeutic approaches have been investigated. Areas covered: In this manuscript, the literature data regarding the advances in drug treatment for patients with mesothelioma are critically reviewed, focusing particularly on immunotherapy and targeted therapy. Expert opinion: The latest findings on immunotherapy and targeted therapy are changing the therapeutic armamentarium for mesothelioma. However, mesothelioma comprises genomically different subtypes and the phenotypic diversity combined with the rarity of this disease represents a major criticality in developing new effective therapies. Although the first clinical data are encouraging, the treatment's stratification by molecular characteristics for mesothelioma is only at the beginning. Luckily, the rapid improvement of understanding the biology of mesothelioma is producing new opportunities in discovering new therapeutic targets to test in pre-clinical settings and to transfer in the clinical setting. In this evolving scenario, the future perspectives for mesothelioma patients seem really promising.